2021
DOI: 10.3390/ijerph182212097
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Co-Agglomeration and Air Pollution Reduction: An Empirical Evidence Based on Provincial Panel Data

Abstract: Industrial co-agglomeration plays a significant role in the moving up of the manufacturing industry in the value chain and in transforming China from a manufacturing giant into a world manufacturing power. This study establishes a co-aggregation index to explore spatio-temporal changes of the co-agglomeration between manufacturing and producer services in 30 provinces of China from 2004 to 2019. Furthermore, we use spatial Durbin model to analyze the impact of industrial co-agglomeration on air pollution reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The area's industrial pollution discharge is directly impacted by changes in many social and economic aspects, as shown by the direct influence. In contrast, the region's shifting social and economic conditions have an impact on the release of industrial pollutants into nearby areas, which is what the indirect effect indicates (Zhuang et al, 2021). Therefore, this study analyzes the indirect influence, direct influence, and total influence of the SPDM model to further evaluate the geographical interaction of the influencing elements of industrial pollution (Table 3).…”
Section: Regression Resultsmentioning
confidence: 99%
“…The area's industrial pollution discharge is directly impacted by changes in many social and economic aspects, as shown by the direct influence. In contrast, the region's shifting social and economic conditions have an impact on the release of industrial pollutants into nearby areas, which is what the indirect effect indicates (Zhuang et al, 2021). Therefore, this study analyzes the indirect influence, direct influence, and total influence of the SPDM model to further evaluate the geographical interaction of the influencing elements of industrial pollution (Table 3).…”
Section: Regression Resultsmentioning
confidence: 99%
“…Moran’s I statistics showed that the spatial distribution of carbon sinks in the counties (districts) of Shaanxi Province was not random, but that there was a significant positive global spatial autocorrelation. Therefore, the use of traditional measurement models would cause the endogenous problems of the model to cause errors in the estimation results, and fail to provide effective policy recommendations [ 37 ]. This paper analyzed the results of the spatial panel Durbin model of the dual fixed effects of carbon sinks in time and space.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [31] believe that the co-agglomeration of producer services and manufacturing can promote carbon intensity reduction in regions with reasonable resource allocation. Based on Chinese provincial panel data from 2004 to 2019, Zhuang et al [32] analyze a regional difference of "high in the east and low in the west" in the co-agglomeration of effective service and manufacturing industries in China. Additionally, industrial co-agglomeration can significantly reduce air pollution using a spatial econometric model, and the air pollution reduction from industrial co-agglomeration has a significant spatial spillover effect.…”
Section: Industrial Co-agglomeration and Carbon Productivitymentioning
confidence: 99%